ENT 530 Social Media Portfolio: Belike Pineapple / Nabila Hidayah Mohd Saidi - Mohd Saidi, Nabila Hidayah (2021)
The business itself is managed by the three sisters where the idea came out after a survey is made and the results was that this kind of product (necklace) is nowhere to be found yet in Malaysia. Most of the shop that sell the exact custom-made necklace are from outside of the country for instance Indonesia. Proudly said, they gave an inspiration to start the business here in Malaysia. Thus, it is such a great idea to take this opportunity to be the first group in selling this kind of necklace. The top position in managing the business is me myself, Nabila Hidayah Binti Mohd Saidi, helped by another two siblings Nadia Hidayah Binti Mohd Saidi and Najihah Hidayah Binti Mohd Saidi. The task to shape a copper wire into a word is made by Nadia while marketing is managed by Nabila. All those masterpiece pictures and videos of our product that are posted online are captured and recorded by Najihah.